Pembelajaran muhadatsah melalui project-based learning - Fitri, Nurul; Supriadi, Rinaldi; Ali, Mad (Universitas Lampung, 2023)
Muhadatsah learning in class X-AKL SMK Daarut Tauhiid Boarding School is carried out through project-based learning. Students have more real learning experiences, namely by practicing muhadatsah by making video projects which will be uploaded on the YouTube channel so that it provides the benefit of the wider community as a comparison or intensive learning. The gap in this study is focused on muhadatsah learning through project-based learning where the learning process is student-centered to gain knowledge and skills in learning. This study aims to analyze how muhadatsah learning is through project-based learning starting from planning, implementation process, and evaluation. Data collection was carried out by observation, interview, and documentation methods. In this study, researchers used descriptive qualitative methods, namely research methods by describing muhadatsah learning through project-based learning. The study results showed that muhadatsah learning through project-based learning in class X-AKL of Daarut Tauhiid Boarding School Vocational School with stages or paths that students must do during learning is quite clear and structured. Success can be seen in this project-based learning, where students actively collaborate, communicate, ask questions, and express opinions. Meanwhile, the drawback is that it requires a long time and limited media for making projects. From these results, it is suggested to be more intensive in monitoring the work of students' assignments so that time can be more effective at each meeting and to ask permission for media access to student dormitory supervisors.Keywords: Learning, muhadatsah, project-based learning